Microbial Control of Musca domestica (Diptera: Muscidae) with Selected Strains of Beauveria bassiana - Lecuona, Roberto Eduardo (2005)
Nineteen strains and species of entomopathogenic fungi were examined for their potential as biological control agents of the house ßy, Musca domestica L. Bioassays against larvae, pupae, and adult males and females in small containers indicated Þve strains of Beauveria bassiana (Bals.) Vuill. were relatively more virulent. Three of the virulent strains, chosen for efÞciency of production in a rice-based, diphasic fungal production system, were further evaluated by mixing spore-contaminated rice residue with sugar and tested as a food bait for adult ßies in a 33-m3 walk-in chamber. Up to 90% mortality was obtained within 15 d of exposure. The results indicate bait formulations of the most virulent and aggressive strain should be further developed and studied